Richer histories for more relevant policies: 42 years of tree cover loss and gain in Southeast Sulawesi, Indonesia. (12th August 2016) - Kelley, Lisa C.; Evans, Samuel G.; Potts, Matthew D.
Abstract: Understandings of contemporary forest cover loss are critical for policy but have come at the expense of long‐term, multidirectional analyses of land cover change. This is a critical gap given (i) profound reconfigurations in land use and land control over the past several decades and (ii) evidence of widespread 'woodland resurgence' throughout the tropics. In this study, we argue that recent advancements within the field of land change science provide new opportunities to address this gap. In turn, we suggest that multidecadal and multidirectional analyses of land cover change can facilitate richer social analyses of land cover change and more relevant conservation policies and practice. Our argument is grounded in a case study from Southeast Sulawesi, Indonesia. Using a novel analytical platform, Google Earth Engine, and open access to high‐quality Landsat data, we map land cover change in Southeast Sulawesi, Indonesia, from 1972 to 2014. We find that tree cover loss constitutes the single largest net change over the period 1972–2014 but that gross rates of tree cover gain were three times higher than gross loss rates from 1972 to 1995 and equivalent to loss rates from 1995 to 2014. We suggest the smallholder tree crop economy likely produced both forest loss and Imperata grassland restoration in this region. This case points to the need to expand rather than collapse the baselines used to study carbon and biodiversity change in tropical regions. It also demonstrates the possible utility of applying such methods to other regions.